Relevance of Biofilms in the Pathogenesis of Shiga-Toxin-Producing Escherichia coli Infection. (12th November 2013) - Angel Villegas, Natalia; Baronetti, José; Albesa, Inés; Polifroni, Rosana; Parma, Alberto; Etcheverría, Analía; Becerra, Maria; Padola, Nora; Paraje, Maria
Abstract : The present study was designed to determine the relationships among biofilm formation, cellular stress and release of Shiga toxin (Stx) by three different clinical Shiga toxin-producing Escherichia coli (STEC) strains. The biofilm formation was determined using crystal violet stain in tryptic soy broth or thioglycollate medium with the addition of sugars (glucose or mannose) or hydrogen peroxide. The reactive oxygen species (ROSs) were detected by the reduction of nitro blue tetrazolium and reactive nitrogen intermediates (RNI) determined by the Griess assay. In addition, the activities of two antioxidant enzymes, superoxide dismutase (SOD) and catalase (CAT), were studied. For the cytotoxicity studies, Vero cells were cultured with Stx released of STEC biofilms. The addition of sugars in both culture mediums resulted in an increase in biofilm biomass, with a decrease in ROS and RNI production, low levels of SOD and CAT activity, and minimal cytotoxic effects. However, under stressful conditions, an important increase in the antioxidant enzyme activity and high level of Stx production were observed. The disturbance in the prooxidant-antioxidant balance and its effect on the production and release of Stx evaluated under different conditions of biofilm formation may contribute to a better understanding of the relevance of biofilms in the pathogenesis of STEC infection.